Strategi Bernegosiasi Bisnis Berbasis Konsep Budaya Jepang: Kajian Sosiopragmatik - Ni Made Andry Anita Dewi; Ni Putu Luhur Wedayanti (Program Studi Sastra Jepang, Fakultas Ilmu Budaya, Universitas Udayana, 2025)
Negotiating strategy plays an important role in deciding a contract, project, or other important decision in the company. The success or failure of an agreement depends on the negotiation strategy used by the speaker. This study examines the speech acts used by the characters in the drama Eigyou Buchou Kira Natsuko as a business negotiation strategy in Japanese. This drama is a corporate genre which was produced in 2016. This research uses the theory of illocutionary speech acts according to Searle and is supported by the classification of communication strategies in the field pragmatics by Shimizu. The results of this study are expected to be useful for Japanese language learners who enter the business or office world. The use of Japanese, including speech related to negotiation strategies in the corporate environment, is strongly influenced by the speech acts of the participants. In addition to the speech acts used, Japanese cultural concepts can also influence whether or not an agreement is realized. Therefore, the results of this study are expected to provide an overview and enrich knowledge regarding negotiation strategies based on the fairly complex concept of Japanese culture